Ficha limpa: decisões do supremo tribunal federal, do tribunal superior eleitoral e judicialização da política - Abreu, Daniel Borges de (2012)
This dissertation attempts to evaluate the existence and importance ofnot juridical motivations in two major trials concerning the applicability of the Complementary Law no. 135/2010, also known as the Lei da Ficha Limpa. Search check, in the votes of the judgesof the Supremo Tribunal Federaland the Tribunal Superior Eleitoral, if there was to carry out calculations of risk of a political nature. Still, there is the intention of identifying the main thematic lines of not juridical manifestation, and check if they, by themselves, are able to place the judges in favor oragainst the applicability of the Lei da Ficha Limpain 2010. From the theoretical perspective, findthe origins of the judiciary, its relationship with the executive and legislature, and are discussed theories on constitutionalism and the constitutional judicial rewiew. The judicialization of politics,in its typefrom without, occupies a central position, and is directly related to the performance of the judiciary in adjudicating cases involving electoral competition. The work also weaves the path of the Lei da Ficha Limpasince its popular initiative, reporting passage through the legislative and executive branches and the arrival of the judiciary. Upon transcription of excerpts from each of the votes took place on the Supremo Tribunal Federal and the Tribunal Superior Eleitoralsets the standard decision of both courts, highlighting the main topics of notlegal discussion. Demonstrates that the judicialization of politics in Brazil,judgments about the rules of electoral competition, an environment that allows you to large expansion.